The Effects of Implementing Online Transportation Quota Limits in Surabaya City - Handayani, Triana Dianita; Wike; Zauhar, Soesilo; Mardiyono (The journal of contemporary issues in business and government, 2021)
The introduction of 4.0 Industrial Revolution has led to several changes in the policies of Indonesia concerning transportation. This is evident with the emergence of online transportation system such as Gojek and Grabcar in 2010. However, several challenges have been observed in its operations such as inappropriate regulations, competition between driver-partners, as well as negative impacts on the welfare of these driver- partners, especially due to their inability to for the cars they use for the business and these require adequate administrative policies. In order to mitigate these problems, the government formulated policies to regulate the existence of online transportation as well as the welfare of partners by making provisions for quota limits. This research was, therefore, conducted to determine the effect of this initiative using a qualitative descriptive approach. The results showed limiting online transportation quotas has the ability to increase driver's partners’ income and, consequently, improve their welfare.